And now what shall become of us without any barbarians? : Torture and abuse of power as an allegory of the relationship between coloniser/colonised in Coetzee's Waiting for the Barbarians - Pittella, Flavia Daniela (2006)
In Waiting for the Barbarians by Coetzee it is very easy to trace every issue one could possible read as regards empire, authoritarian governments, torture, abuse of power; denial and self denial, but also humanity, the gathering in borders of the people who in the end, are bound to share the land and live in peace, as the Magistrate describes when he charges a torturer “there were no border troubles here before you came” (COETZEE, 1982: 125). It is also a novel about resistance and the capacity latent in all of us to act freely, to try and change the course of our personal or collective history, more often than not to one’s cost. Needless to say, my reading of this novel is in Derrida’s terms “a limited work, but with its own field and framework. A work possible only in a historical, political, theoretical, etc. situation that is highly determined” (DERRIDA, 1981: 63). Our country and its recent past cry out from the pages as, once and again, the tortured and the torturers in this story mirror those we have known to exist in Argentina. Given that it is so complex a novel and coming to terms with length and time, I will, in this paper, only attempt a first bird’s eye view at the issues of the search for the truth (confession), torture and abuse of power in the discourse of the narrator of the novel, in the light of Bahktin’s concept of narrator as always having another’s speech. (BAHKTIN, 1981, 313)